SUPERVISI PEMBELAJARAN KOLABORATIF DI LEMBAGA PAUD: ANALISIS IMPLEMENTASI DAN REKOMENDASI MODEL SUPERVISI KLINIS - Andika Aprilianto; Resi Rosialianisa; Ibrahim Bafadal; Ahmad Nurabadi (STKIP Pesisir Selatan, 2026)
This study analyzes instructional supervision practices at an Islamic-based kindergarten in Malang Regency with a strong commitment to educational quality and formulates a contextual supervision model as a guide for future development. A Problem-Based Learning (PBL) approach was used to identify gaps between current supervision practices and modern supervision standards, through direct observation, in-depth interviews, and document review, triangulated across sources, methods, and theories. Institutional capital is strong, principal commitment and teacher dedication are high, yet the supervision system requires significant strengthening: the approach remains directive, scheduling is unstructured, standardized observation instruments are unavailable, and documentation is inconsistent. Seven of eight analyzed aspects show high gaps. A clinical supervision model with a collaborative approach is recommended, comprising six stages: conceptual preparation; joint program planning; development of the observation instrument; implementation of the clinical supervision cycle (pre-observation, observation, analysis, post-observation); portfolio documentation; and periodic PDCA-based evaluation. This model is intended as a practical, adaptable guide for similar resource-constrained Islamic-based PAUD institutions.